Maxillomandibular relationship record for complete arch/mouth implant restorations using putty-elastomeric occlusion rim at healing abutment level - Pravinkumar G Patil; Smita Nimbalkar-Patil (Wolters Kluwer Medknow Publications, 2015)
Introduction: Recording of the maxillomandibular relationship (MMR) in implant complete arch restorations usually necessitates removal of the healing abutments to attach the record bases, which makes the procedures tedious and time-consuming. Materials and Methods: This article describes the procedure of recording of MMR for complete mouth rehabilitation with the help of the putty elastomeric record base cum occlusion rim reinforced with the acrylic resin framework. This technique records the MMR without removing the healing abutments from mouth and without attaching the acrylic-resin record base with wax occlusion rim. Results: The use of putty-elastomeric occlusion rim provides stable interocclusal records for implant supported complete arch (or mouth) rehabilitation. Conclusion: Maxillomandibular relationship records made with the present technique is less time-consuming and accurate with less chances of distortion of the MMR records.